Chronique juridique - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1986)
The author briefly comments on certain lawsuits published in Jurisprudence Express in 1985. This summary, intended for the broker or layman, does not aim to give full details of the lawsuits examined; rather it focuses on the main facts and the sentence rendered. This article is a work tool which may prove useful in helping readers understand the sentence and its ramifications.